2006
DOI: 10.1007/s00534-006-1123-3
|View full text |Cite
|
Sign up to set email alerts
|

Gallbladder cancer: surgical results after cholecystectomy in 25 patients with lamina propria invasion and 26 patients with muscular layer invasion

Abstract: According to these results, cholecystectomy is not sufficient treatment for gallbladder carcinoma with muscular-layer invasion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Some authors reported long-term survival after simple cholecystectomy and did not recommend radical resection for T1b disease [18,19], and others reported the five-year survival rate was 37.5-68% after simple cholecystectomy for T1b disease. As a consequence, they advocate aggressive surgery (extended cholecystectomy, wedge resection of gallbladder bed or segment IVb and V resection, N1 lymph node dissection) for pT1b disease [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors reported long-term survival after simple cholecystectomy and did not recommend radical resection for T1b disease [18,19], and others reported the five-year survival rate was 37.5-68% after simple cholecystectomy for T1b disease. As a consequence, they advocate aggressive surgery (extended cholecystectomy, wedge resection of gallbladder bed or segment IVb and V resection, N1 lymph node dissection) for pT1b disease [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors in the past have suggested that no further surgery is required after simple cholecystectomy 6, 19, 20; this based on good results in patients with p T1b after simple cholecystectomy 21, 22 as well as the absence of nodal disease in patients with T1 disease 23, 24. However, it now seems that the advocates for radical revision surgery even for T1b and T2 disease 25–29 are being proved correct based on studies examining lymphovascular invasion 30–32.…”
Section: Discussionmentioning
confidence: 99%
“…Hematogeneous metastases to GB initially occur as small flat nodules below the mucosal layer and then they grow as a pedunculated nodule and resemble a primary GB carcinoma . It is well known that cholecystectomy is not sufficient treatment and more radical surgery is required for GB carcinoma with muscular‐layer invasion or more advanced disease . Furukawa et al reported that 1 of 31 resected GB polypoid lesions of less than 3 cm was a metastasis from RCC, which was detected on both unenhanced and enhanced CT scans.…”
Section: Discussionmentioning
confidence: 99%